Long-run growth uncertainty - Pei Kuang; Kaushik Mitra (University of Birmingham, Birmingham Business School, 2016)
Observed macroeconomic forecasts display gradual recognition of the long-run growth of endogenous variables (e.g. output, output per hour) and a positive correlation between long-run growth expectations and cyclical activities. Existing business cycle models appear inconsistent with the evidence. This paper presents a model of business cycle in which households have imperfect knowledge of the long-run growth of endogenous variables and continually learn about this growth. The model features comovement and mutual influence of households' growth expectations and market outcomes, which can replicate the evidence, and suggests a critical role for shifting long-run growth expectations in business cycle fluctuations.
Keywords: E32; D84; 330; Trend; Expectations; Business Cycle